Tinjauan Hukum Islam Tentang Penyebaran Drama Korea Melalui Media Telegram - Syaripudin, Enceng Iip; Hadriyanti, Nabila (Jurnal Hukum Ekonomi Syariah, 2024)
This research aims to examine the views of Islamic law on the phenomenon of spreading Korean dramas via Telegram media. The distribution of digital content such as Korean dramas via social media platforms has become an increasingly widespread practice among society. However, this raises questions regarding the legality of this practice from the perspective of Islamic law. The research method used is library research with a qualitative approach. Primary data was obtained from Islamic law books (fiqh) and ushul fiqh, as well as fatwas from ulama or religious institutions. Meanwhile secondary data comes from books, journals, articles and other literature related to Islamic law and the dissemination of digital content. The research results show that Islamic law views the spread of Korean dramas via Telegram media as an action that has potential legal implications. Several aspects that need to be considered are copyright issues, socio-cultural impacts, as well as ethical and morality issues contained in Korean drama content. Based on the analysis of maqasid al-syariah (goals of Islamic law), the distribution of Korean dramas via Telegram can potentially provide benefits as well as cause harm (danger) to society. Therefore, efforts are needed to respond to this phenomenon wisely, guided by the principles of Islamic law, such as protecting religion, soul, reason, property and honor. Keywords: Islamic Law, Distribution of Korean Dramas, Telegram Media